PENETAPAN KEBIJAKAN PENGHAPUSAN PIUTANG PAJAK DAERAH DAN RETRIBUSI DAERAH - Wan Eva Yuliani (Universitas Riau, 2016)
Determination of Regional Tax Receivables Elimination Policy and Levies. The purpose of this study was to analyze the process or stages of policy formulation, knowing the factors that affect, knowing the actors involved and the role of actors in the formulation of the policy. The informants are the Department of Revenue and the taxpayer Bengkalis. Data obtained from interviews, observation and documentation. Based on the results, it can be concluded that the process of formulating the draft local regulations is not ideal and can be categorized into the institutional model.